2012
DOI: 10.1016/j.msea.2012.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundaries in ultrafine grained materials processed by severe plastic deformation and related phenomena

Abstract: Grain boundaries in ultrafine grained (UFG) materials processed by severe plastic deformation (SPD) are often called "non-equilibrium" grain boundaries. Such boundaries are characterized by excess grain boundary energy, presence of long range elastic stresses and enhanced free volumes. These features and related phenomena (diffusion, segregation, etc.) have been the object of intense studies and the obtained results provide convincing evidence of the importance of a non-equilibrium state of high angle grain bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
271
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(288 citation statements)
references
References 133 publications
(223 reference statements)
10
271
0
7
Order By: Relevance
“…In addition, recent studies showed that diffusion or segregation processes in ufg materials are considerably influenced by the highly-distorted non-equilibrium grain boundaries [65][66][67][68]. The vacancy-type free volumes are supposed to be mainly located in the grain boundary regions, thus enhancing grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies showed that diffusion or segregation processes in ufg materials are considerably influenced by the highly-distorted non-equilibrium grain boundaries [65][66][67][68]. The vacancy-type free volumes are supposed to be mainly located in the grain boundary regions, thus enhancing grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…[146,147] Some experimental evidence is now available for the positive slope at very small grain sizes [148] and generally the strengthening is attributed to the presence of significant grain boundary segregation at grain sizes smaller than ~100 nm. [149,150] This is an area requiring further investigation but generally it is reasonable to anticipate SPD materials will exhibit improved strength and improved functional properties associated not only with their ultrafine grains but also with other nanostructural features that are not generally available in conventional coarse-grained materials. [151] VI.…”
Section: Superstrength By Spdmentioning
confidence: 99%
“…The processed metals generally demonstrate an enhancement of the physical and mechanical characteristics through significant grain refinement and the intensive introduction of point and line defects. Recent reviews described the importance of the different types of defects produced though SPD processing and the superior properties that may be achieved in UFG materials [4,5].…”
Section: Introductionmentioning
confidence: 99%